Analysis Of The Role Of Kpai To Protect Violence Against Children - Ansori Maulana; Lidya Rahmadhani Hasibuan (International Journal of Society and Law, 2024)
KPAI is a state institution whose special task is to supervise the implementation of child protection in Indonesia, which is an obligation that must be upheld and implemented by the laws of the Republic of Indonesia. Violence is a mere behavior carried out by someone against another person to cause psychological or physical harm or injury. Punishment is not only expected to provide a deterrent sanction against the perpetrator. This research uses a normative juridical approach because the author only studies and analyzes based on previously existing cases obtained either from books, journals, or online media which are then analyzed according to the data. This writing focuses on legal protection for children in cases of violence in Indonesia. We as a society or parents must protect children from perpetrators who are victims of violence. The perpetrator always has a way to commit a crime. If the perpetrator of a crime of violence is caught, punish the perpetrator as harshly as possible, and for victims who experience violence, here too the victim also experiences mental pressure and severe trauma. You also have to help with treatment so that the child becomes confident again and can carry out the activities they normally do. Violence perpetrated against a child has several impacts, such as the child becoming disturbed in his/her education, the child becoming aggressive and even dying due to the physical damage experienced by the child. To reduce the level of violence against children, it is necessary to raise the age limit for marriage for children. Because the ideal marriage age for women is 21 years and for men 24 years, the data was obtained from the BKKBN campaign so that families grow up.